2021
DOI: 10.1021/jacs.1c09822
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Phospholipidation of Cationic Polymers Facilitates Systemic mRNA Delivery to Spleen and Lymph Nodes

Abstract: Polymers represent a promising therapeutic platform for extrahepatic messenger RNA (mRNA) delivery but are hampered by low in vivo efficacy due to polyplex serum instability and inadequate endosomal escape following systemic administration. Here, we report the rational design and combinatorial synthesis of zwitterionic phospholipidated polymers (ZPPs) via cationic polymer postmodification by alkylated dioxaphospholane oxides to deliver mRNA to spleen and lymph nodes in vivo. This modular postmodification appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 57 publications
4
93
0
Order By: Relevance
“…4 Therefore, the usage of mRNA therapeutics requires safe, effective, and stable delivery systems to protect from degradation and allow cellular uptake and functionality. 1,[5][6][7][8] In clinical trials, both viral and non-viral vectors are used for systemic delivery of mRNA. 9 Viral vectors have high transfection efficiency and higher specicity for cell targeting, but have several intrinsic limitations including delayed cellular immune response, the possibility of carcinogenesis, and limited opportunity for repeated administration due to acute inammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, the usage of mRNA therapeutics requires safe, effective, and stable delivery systems to protect from degradation and allow cellular uptake and functionality. 1,[5][6][7][8] In clinical trials, both viral and non-viral vectors are used for systemic delivery of mRNA. 9 Viral vectors have high transfection efficiency and higher specicity for cell targeting, but have several intrinsic limitations including delayed cellular immune response, the possibility of carcinogenesis, and limited opportunity for repeated administration due to acute inammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, polyplexes prepared from the ZPPs were found to accumulate in the spleen and lymph nodes of C57BL/6 mice and generated high protein expression following intravenous administration, while the parent polycations failed in in vivo mRNA delivery. 32 Conceptually related studies published by Ahern et al described a group of brush-like polymers prepared by ring opening of poly(glycidyl methacrylate) (polyGMA) using primary amines with different alkyl chain lengths in which the alkyl chains effectively reduce the charge density (i.e., overall charge character) of the polymers, which improved the cytocompatibility while still producing a transfection performance that exceeded that of PEI in HEK293 cells. 33 While the examples above show the value of adjusting the hydrophilic/lipophilic balance of polycations for polyplex formation and transfection, other studies suggest that such approaches are sensitive to the specific chemistry and architecture selected.…”
Section: Interplay Of Polymer Architecture and Compositionmentioning
confidence: 99%
“…Screening these ZPPs for their utility to deliver mRNA to IGROV1 cells showed that the polymers prepared using the amines denoted A5–A7 produced greater levels of expression relative to ZPPs prepared from the other amines. Notably, polyplexes prepared from the ZPPs were found to accumulate in the spleen and lymph nodes of C57BL/6 mice and generated high protein expression following intravenous administration, while the parent polycations failed in in vivo mRNA delivery . Conceptually related studies published by Ahern et al described a group of brush-like polymers prepared by ring opening of poly­(glycidyl methacrylate) (polyGMA) using primary amines with different alkyl chain lengths in which the alkyl chains effectively reduce the charge density (i.e., overall charge character) of the polymers, which improved the cytocompatibility while still producing a transfection performance that exceeded that of PEI in HEK293 cells …”
Section: Interplay Of Polymer Architecture and Compositionmentioning
confidence: 99%
“…They found that sa-mRNA was more effective than mRNA in protection against infection, and sa-mRNA combined in a trivalent formulation could protect against sequential H1N1 and H3N2 challenges. Liu et al [ 70 ] synthesized zwitterionic phospholipidated polymers (ZPPs) to deliver mRNA to spleen and lymph nodes ( Figure 4 ). This modular modification approach produced tunable zwitterionic species for serum resistance and introduction of alkyl chains simultaneously enhanced endosomal escape, which transformed deficient polymers into efficient zwitterionic mRNA carriers.…”
Section: Mrna Carriersmentioning
confidence: 99%
“… ZPPs used for efficient mRNA delivery into spleen and lymph nodes [ 70 ]. A. Phospholipidation transformed polycations to efficient zwitterionic mRNA carriers enabling protein expression in the spleen and lymph nodes; B. the synthetic route toward zwitterionic polymers PAn-xPm.…”
Section: Mrna Carriersmentioning
confidence: 99%